Smart City of Tomorrow: Kuala Lumpur's Evolution through Al-Farabi's Vision of Good Governance - Fadhlurrohman, Abid; Al-Giffari, Haekal Adha (International Journal of Sustainability in Research, 2024)
This study delves into Kuala Lumpur's smart city evolution, inspired by Al-Farabi's ideal of good governance, as outlined in the Kuala Lumpur Smart City Master Plan 2021–2025. Overseen by Dewan Bandaraya Kuala Lumpur (DBKL), this initiative marries technological innovation with Al-Farabi's principles of a virtuous society, aiming for a development that is both inclusive and culturally resonant. It underscores the importance of centralized communication for effective urban planning and advocates for using social media to boost public engagement. Significantly, it calls for embedding Islamic values in policymaking, ensuring the project's ethical foundation. This synthesis of modernity and tradition positions Kuala Lumpur as a model for smart cities worldwide, promising a future where technology and moral governance coalesce to enhance citizen well-being.